2020
DOI: 10.7150/jca.38386
|View full text |Cite
|
Sign up to set email alerts
|

GINS2 affects cell viability, cell apoptosis, and cell cycle progression of pancreatic cancer cells via MAPK/ERK pathway

Abstract: Background and Objective: GINS complex subunit 2 (GINS2), a member of the GINS complex, is involved in DNA replication. GINS2 is upregulated in a variety of aggressive tumors, such as leukemia, breast cancer, and cervical cancer. However, the role of GINS2 in pancreatic cancer has still remained elusive. In this study, PANC-1 and BxPC-3 cell lines were chosen to perform experiments in vitro. Additionally, the effects of GINS2 interference on the cell viability, cell apoptosis, cell cycle, and tumor growth in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Overexpression of UBE2T and PTTG1 promotes HCC cell growth, migration and invasion through activating Akt pathway [69,70]. GINS2 is a member of the GINS complex and participates in DNA replication and cell cycle regulation in most tumors, such as pancreatic cancer [41], bladder cancer [71], and lung cancer [72]. Bioinformatic analysis showed that both individual GINS2 and the whole GINS complex could be prognostic biomarkers for HCC [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of UBE2T and PTTG1 promotes HCC cell growth, migration and invasion through activating Akt pathway [69,70]. GINS2 is a member of the GINS complex and participates in DNA replication and cell cycle regulation in most tumors, such as pancreatic cancer [41], bladder cancer [71], and lung cancer [72]. Bioinformatic analysis showed that both individual GINS2 and the whole GINS complex could be prognostic biomarkers for HCC [73].…”
Section: Discussionmentioning
confidence: 99%
“…TYMS is an essential rate-limiting enzyme in the nucleotide metabolism, and is involved in DNA synthesis [40]. GINS2 knockdown also inhibits cell viability and induces cell cycle arrest in pancreatic cancer cells [41]. Thus, abnormal cell cycle may be the intrinsic related mechanism of NASH and HCC.…”
Section: Functional and Pathway Enrichment Analysismentioning
confidence: 99%
“…In recent decades, GINS2 has been involved in the development of various cancers, such as pancreatic, lung, and thyroid cancers [15,17,32]. Zhang et al demonstrated that GINS2 elevated cell growth and cell cycle progression by activating the MAPK/ERK pathway in pancreatic cancer cells [17].…”
Section: Discussionmentioning
confidence: 99%
“…GINS complex subunit 2 (GINS2) serves as an oncogene in cancer genesis by enhancing cell growth and repressing cell apoptosis in various cancers, including thyroid, lung, and pancreatic cancers [15][16][17]. It has also been associated with the progression of OC by regulating cell growth and apoptosis [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…MAPK regulates cell proliferation, differentiation, development and apoptosis through signaling transmission ( 23 , 40 ). In our previous study, it was found that GINS2 interference inhibited cell viability, induced cell cycle arrest and promoted cell apoptosis in pancreatic cancer cell lines via the MAPK/ERK pathway ( 41 ). In the present study, the relationship between GINS2 and MAPK pathway was investigated in TC cells.…”
Section: Discussionmentioning
confidence: 99%